Analisis Investasi Opportunity Set dan Dividen sebagai variabel Moderasi dalam Faktor Penentu Nilai Pemegang Saham - Nurul Fatikhatul Khusna; Aida Nahar (Jurnal Dinamika Ekonomi dan Bisnis, 2023)
The objective of the research is to examine the influence of Free Cash Flow, Funding Decisions, and Company Size on Shareholder Value with Investment Opportunity Sets and Dividends as moderating variables. This research was quantitative research. The population in this study was manufacturing companies in the consumer goods industry sector that report financial reports on the Indonesian stock exchange for the 2018-2020 period. The sampling technique used non-probability sampling with a saturated sample/census technique. The data analysis technique used multiple linear regression analysis methods with Moderated Regression Analysis (MRA). The results of this research are that the investment decision set is a moderating variable between company size and shareholder value. This means that company size will influence shareholder value if there is a set of investment decisions. If there are no moderating factors, then the determining factor for shareholder value is the funding decision. The free cash flow variables and company size do not affect shareholder value. Meanwhile, dividends are not a moderating variable in determining shareholder value. And the set of investment decisions does not moderate the relationship between free cash flow and funding decisions on shareholder value.